28 GHz MMIC resonant tunnelling diode oscillator of around 1mW output power. Issue 13 (1st June 2013) - Wang, J.; Wang, L.; Li, C.; Romeira, B.; Wasige, E.
Abstract : Presented is a monolithic microwave integrated circuit (MMIC) resonant tunnelling diode (RTD) oscillator that employs two In0.53 Ga0.47 As/AlAs RTDs (5 × 5 µm 2 ) in parallel. The oscillator works at 28.7 GHz with −0.7 dBm output power. The phase noise was −95 dBc/Hz at 100 kHz and −114 dBc/Hz at 1 MHz offset. This reported work demonstrates the potential of RTD oscillators in achieving high output power at high frequencies by utilising suitable power maximising and combining techniques.